2008
DOI: 10.1037/0096-1523.34.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Speed limits: Orientation and semantic context interactions constrain natural scene discrimination dynamics.

Abstract: The visual system rapidly extracts information about objects from the cluttered natural environment. In 5 experiments, the authors quantified the influence of orientation and semantics on the classification speed of objects in natural scenes, particularly with regard to object-context interactions. Natural scene photographs were presented in an object-discrimination task and pattern masked with various scene-tomask stimulus-onset asynchronies (SOAs). Full psychometric functions and reaction times (RTs) were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 75 publications
(209 reference statements)
1
18
0
Order By: Relevance
“…This is true even for short exposure durations and speeded response times, indicating parallel processing of object and context information. Other experiments have demonstrated that manipulation of color [59], proportions [41] and orientation [43] in scenes hamper the recognition of a target object. We failed to find impaired object categorization with an inverted background.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is true even for short exposure durations and speeded response times, indicating parallel processing of object and context information. Other experiments have demonstrated that manipulation of color [59], proportions [41] and orientation [43] in scenes hamper the recognition of a target object. We failed to find impaired object categorization with an inverted background.…”
Section: Discussionmentioning
confidence: 99%
“…We failed to find impaired object categorization with an inverted background. According to Rieger et al [43], orientation effects are strongest if the context is rotated by 90°. They showed that rotation by 180° has a weaker effect in natural scene discrimination and suggest some “orientation compensation” mechanisms that allow faster processing of inverted scenes than for intermediate rotation angles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, context (or global scene) congruence has generally been shown to have a significant effect on classification accuracy and speed [26], [27]. In the ANID database, images of animals were taken in their natural habitats or in zoo environments coming close to the natural habitat of the animals.…”
Section: Introductionmentioning
confidence: 99%
“…Processing in the Brain (Jantzen et al 2007;van Berkum et al 2008) Cognition, Perception and Emotion Shaped and Filtered by Cultural Context (Choi et al 1999;Heine et al 1999;Markus and Kitayama 1991;Nisbett et al 2001;Norenzayan et al 2002) Ecological/Bounded Rationality Research program (Camerer and Fehr 2006;Hutchinson and Gigerentzer 2005) Brain Development Affected by Social and Cultural Experience (Eisenberg 1999;Schlaug et al 2005;Broad et al 2006) The Primacy of Action in Context (Costall et al 2004;Tremoulet and Feldman 2006;Wilson 2002) Everyday Cognition Studies (Hazlehurst et al 2007;Margrett and Willis 2006;Rogoff and Lave 1984) Social Neuroscience: Social Effects on Brain (Adolphs 2003;Todorov et al 2006;Olsson and Phelps 2007) Contextual Effects on Cognition (Rieger et al 2008;Hagoort and van Berkum 2007) Situated/Distributed/ Embodied social cognition (Nardi 1996;Niedenthal et al 2005) In each cell, three representative examples of the specific research agenda are detailed mind as an area of research in cognitive sciences with remarkable scientific potential, from multi-level methodological and theoretical perspectives, that manifestly are out of reach of the old limits of orthodox computationalism.…”
Section: Context-dependentmentioning
confidence: 98%